THE IMPACT OF FINANCIAL COMPENSATION ON THE PERFORMANCE OF MARKETING EMPLOYEES (Case Study PT. LIEK MOTOR BRANCH MAYOR MUSTAJAB SURABAYA) - Ahmad Habibillah; Sugiharto Sugiharto; Achmad Daengs; Rina Dewi (PT. Mawadaku Sukses Solusindo, 2024)
To achieve this goal, companies need to pay attention to employees in all aspects of their work because this becomes an incentive for employees to carry out their work activities and achieve organizational goals. For this reason, it is natural to pay attention to the whereabouts of employees from the start. Employees who are company assets need to know their needs and desires so that they are expected to be able to produce job satisfaction, good performance and high loyalty to the company so as to achieve company goals. Effective human resource management requires managers to find the best way to employ employees to achieve goals. company. There are many things that can be done to empower good human resources, including efforts that include level education, training, and creating a conducive work situation or environment so that employees feel at home carrying out their work. Compensation is an important aspect in determining employee performance. Company attention is important because employees try to achieve the performance determined by the company. Realizing the importance of compensation for company performance, compensation management should be important. In providing compensation, the timeliness of providing compensation and the amount of compensation given by the company to employees affects employee morale, motivation, work performance and performance. An employee's absolute income level will determine the scale of his life and relative income shows his status and dignity. Therefore, if employees perceive that the compensation they receive is inadequate, this will cause employee morale, motivation, work performance and performance to decline drastically.